2016
DOI: 10.1186/s12866-016-0717-4
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium pseudotuberculosis may be under anagenesis and biovar Equi forms biovar Ovis: a phylogenic inference from sequence and structural analysis

Abstract: BackgroundCorynebacterium pseudotuberculosis can be classified into two biovars or biovars based on their nitrate-reducing ability. Strains isolated from sheep and goats show negative nitrate reduction and are termed biovar Ovis, while strains from horse and cattle exhibit positive nitrate reduction and are called biovar Equi. However, molecular evidence has not been established so far to understand this difference, specifically if these C. pseudotuberculosis strains are under an evolutionary process.ResultsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…The phylogenetic trees separate biovar Ovis from Equi with at least 90% of confidence value, clearly showing it as a monophyletic group ( S2 and S3 Figs). This confirms what has been seen in previous studies [ 32 , 33 , 87 ]. In addition, the Equi from buffalo and horse formed a clade with two different clusters representing each host.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The phylogenetic trees separate biovar Ovis from Equi with at least 90% of confidence value, clearly showing it as a monophyletic group ( S2 and S3 Figs). This confirms what has been seen in previous studies [ 32 , 33 , 87 ]. In addition, the Equi from buffalo and horse formed a clade with two different clusters representing each host.…”
Section: Resultssupporting
confidence: 93%
“…In a previous study, C . pseudotuberculosis was suggested to be under anagenesis and that Ovis would replace Equi [ 87 ]. However, Equi has horse and buffalo as exclusive hosts [ 19 , 31 ] and infections of horses are increasing in frequency in North America [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results are especially significant considering that C. pseudotuberculosis infects a wide range of hosts and produce different clinical manifestations. Furthermore, it was recently suggested that C. pseudotuberculosis biovars have differences at the molecular phylogenetic level, indicating an anagenesis process within the species [ 37 , 49 ]. The evolutionary analysis of conserved genes ( rpoB, gapA, fusA, and rsmE ) suggesting a gradual anagenesis of C. pseudotuberculosis in that study [ 49 ] substantially increases the importance of a molecular technique capable of efficiently separating the biovars Ovis and Equi.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was recently suggested that C. pseudotuberculosis biovars have differences at the molecular phylogenetic level, indicating an anagenesis process within the species [ 37 , 49 ]. The evolutionary analysis of conserved genes ( rpoB, gapA, fusA, and rsmE ) suggesting a gradual anagenesis of C. pseudotuberculosis in that study [ 49 ] substantially increases the importance of a molecular technique capable of efficiently separating the biovars Ovis and Equi. In fact, a pan-genome analysis of fifteen C. pseudotuberculosis strains showed a significant number of genes not shared by both biovars, including remarkable differences in the 16 detected pathogenicity islands [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, Phylogenetic approaches can be applied as methods for the identification of new species formation. It was a goal of a recent work showing events of biological speciation (Oliveira et al, 2016 ), among strains of the C. pseudotuberculosis species, in which it was proposed these strains could be under anagenesis process checking information such as: presence of biovar equi or ovis, evolutionary divergences, number of transition, and transversion substitutions and protein structure analysis.…”
Section: Genomics and Transcriptomicsmentioning
confidence: 99%